U.S. political parties - Hershey, Marjorie Randon; Burden, Barry C., 1971-; Wolbrecht, Christina (CQ Press, 2014)
This book presents the major conceptual approaches to the study of U.S. political parties and the national party system, describing the organization and behavior of U.S. political parties in thematic, narrative chapters that help undergraduate students better understand party origins, historical development, and current operations.